Application of Neural Network for Pattren Recognition of Plants Leaves, ISBN-10 : 3659815772 / ISBN-13 : 978-3659815775 - Abdelhadi Adel; Kadri Ouahab (Lambert Academic Publishing, 2015)
This work appears in pattern recognition in the agronomic domain, especially for the identification of the leaves of plants, while using the adaptive technique of neuronal networks. In this article, we will expose our tool; which is intended for two categories of specialists, the first consisting of researchers in the field of botany, as the second, so all scientists, who may use this work in their own applications. We will expose also, the capacities of generalization of the neuronal networks and their implementation to our problem.